STUDY OF THE SCIENTIFIC BASIS OF IDENTIFICATION OF SELECTED INDUSTRIAL MULBERRY SILKWORM HYBRIDS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Analysis of productivity indicators of half-marked breeds of the world collection of silkworms of the Sericulture Research Institute, improvement of some valuable indicators of selected breeds, the problem of butterflies not emerging from cocoons in half-marked breeds, hybridization among half-marked breeds. selection, the processes of creating combinations, testing the created hybrids in laboratory and production conditions are presented.